Assessment of the management level of coffee farms at Alta Mogiana Paulista - Faleiros, Gabriel Diniz; Bliska, Antonio; Turco, Patrícia Helena Nogueira [UNESP]; Bliska, Flávia Maria de Mello (UNESP - Universidade Estadual Paulista, 2020)
The world demand for high quality coffee is increasing, thus recognizing and promoting quality from the farms to the consumers. The farmer must follow the change in the coffee chain, which is very integrative. Once the farmer does not influence external factors, it must manage its farm from internal components. This paper aims to determine the management level of coffee farms in the Alta Mogiana Paulista, the factors that influence the level, and patterns that reflect local competitiveness. The region produces excellent quality coffee grains and considerable production volume, due the favorable edaphoclimatic conditions, and holds the label of Certified Origin. We used the Management Level Identification Method, including 64 questions, segregated in eight criteria, ranging from one (inferior) to nine (superior) in a grading scale. The method was applied in 80 farms. Other components were also considered: cooperativism, certification, farm size and technical assistance. The rank of the Alta Mogiana Paulista is relatively high (average is 8,5 and median is nine), for all the criteria analyzed, compared to the Sao Paulo State and Brazil. The certification, cooperativism, the search for technical assistance and the participation in technical events resulted in higher management levels. There are more small and median farms in the Alta Mogiana Paulista. Indicators of grain quality management showed high grades, superior than those of Sao Paulo State and Brazil.
Avaliação do grau de gestão dos cafezais da Alta Mogiana Paulista
Keywords: Coffee; Cooperativism; Franca microregion; Management indicators; Quality